2019
DOI: 10.1515/biol-2019-0038
|View full text |Cite
|
Sign up to set email alerts
|

Determining Potential Feed Value and Silage Quality of Guar Bean (Cyamopsis tetragonoloba) Silages

Abstract: This study was carried out to determine the effects of some additives on the potential nutritional value and silage quality of guar bean (Cluster bean = Cyamopsis tetragonoloba) silages. It was hypothesized that the use of cereal grains, molasses and ecomass will reduce silage fermentation pH by increasing lactic acid production and positively improve CP content and silage quality. Four different silage groups were established; (control, grain (5%), molasses (10%) and ecomass+molasses (10%+5%)). Fresh guar bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Such a case then necessitates cluster bean to be used as fodder or in silage. However, since cluster bean is a leguminous crop, sole silage has several drawbacks, thus additives should be used to improve quality attributes of cluster bean silage (Oflaz et al, 2019). Although cluster bean is commonly used in animal feeding (Rai, 2015), there aren't any comprehensive study conducted about mixed silage with maize.…”
Section: Introductionmentioning
confidence: 99%
“…Such a case then necessitates cluster bean to be used as fodder or in silage. However, since cluster bean is a leguminous crop, sole silage has several drawbacks, thus additives should be used to improve quality attributes of cluster bean silage (Oflaz et al, 2019). Although cluster bean is commonly used in animal feeding (Rai, 2015), there aren't any comprehensive study conducted about mixed silage with maize.…”
Section: Introductionmentioning
confidence: 99%
“…While the previous literature has shown that guar meal use has not limited production by Holstein cattle, the effect of forage needs to be evaluated. A major concern is related to palatability issues potentially decreasing intake [16,17]. Other concerns, such as the potential for animal bloat or other types of digestive upset, require animal feed trials, but should not be interpreted as resolved through this Excelbased analysis or the nutritional analysis conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, also on lactating Holstein cattle, demonstrated that guar meal could effectively replace cottonseed (Gossypium hirsutum) meal, but they noted issues with palatability when more than five percent guar meal was fed. The authors also noted that dairy cows and heifers acclimated to taste and odor after a few days, even with rations containing 10-15% guar meal (Salehpour, Qazvinian, and Cadavez, 2012 [16]); and Olfaz, Kilic, and Yavrucu, 2019 [17] attempted to address palatability issues caused by the presence of hydrocyanic acid in young guar beans by mixing them with other grains, molasses, or molasses + ecomass (Ecomass is a feed additive containing 48% CP and 94% dry matter in dark brown powder form, containing powdered fermentation-derived proteins and complementary carbohydrates (bran and corn gluten)) and ensiling the product. The analysis of palatability relied on the measurement of the tannin content of post-fermentation feed [17].…”
Section: Guar As a Potential Foragementioning
confidence: 99%
“…The sensory evaluation of silage was referred to as the Deutsche Landwirtschafts-Gesellschft (DLG) score. 29 Besides, the Fleig score 30 (FS = 220 + (2 × dry matter % − 15) − 40 × pH) and "Quality Evaluation of Silage" (DB50/T 669-2016) were also carried out, and these scoring criteria are shown in the Supporting Information (Tables S2−S4). The evaluation was carried out from several aspects, such as dry material content, pH value, moisture, odor, color, and texture, and the quality class was different according to the method.…”
Section: Examination Of the Characteristics Of Sweet Sorghummentioning
confidence: 99%